OP35 Do HIV services meet the needs of adults diagnosed with HIV at an older age? A qualitative interview study. (13th September 2016) - Bell, S; Doran, T; Adamson, J; Martin, F
Abstract : Background: Historically, younger adults have been the focus of national sexual health/HIV campaigns; however, new HIV diagnoses are increasingly reported in adults aged 50+ years. It is therefore important to investigate whether HIV services are acceptable and accessible to older people. This study aimed to explore accessibility and acceptability through qualitative interviews with service users diagnosed with HIV at age 50+ years and their healthcare providers. Methods: Qualitative interviews with 15 adults (age range 50–67 years) diagnosed with HIV at age 50+ years and 12 healthcare professionals working in sexual/health services (from medical, nursing and psychology backgrounds). The majority of service users were recruited from a high HIV prevalence setting; healthcare professionals were equally recruited from high and low prevalence settings. Results: An over-riding identified theme is that HIV services provide an 'enhanced' service for older people from the point of diagnosis. Service users perceive themselves to be more in control of their health following diagnosis, primarily due to an increased level of support and health monitoring (e.g. frequent blood tests and blood pressure checks, regular clinic appointments) and the adoption of healthier lifestyles. Healthcare professionals identified some advantages for older service users with HIV compared with the general older population, including the detection of future health problems at an earlier stage and the instigation of prompt treatment. Sexual health/HIV services outside high HIV prevalence areas were commonly perceived as youth-orientated. In low prevalence areas, services aim to be age-inclusive but struggle due to financial constraints. The targeting of sexual health/HIV resources towards younger people and HIV risk groups (e.g. men who have sex with men, black Africans, and younger people) was identified as a key contributor to the high proportion of older adults diagnosed at a late stage of disease, particularly for those in low and medium risk groups. Late HIV diagnosis was associated with limited HIV knowledge and a lack of personal risk perception. Conclusion: Once accessed, the needs of older adults appear to be well addressed by HIV services, with exceptional care and support reported in this setting. However, to encourage access to HIV services, national sexual health/HIV campaigns should aim to increase HIV awareness across all age groups, and to promote services as accessible to all.